THE INFLUENCE OF LEMB MUSCLE STRENGTH TRAINING ON LONG JUMP ABILITY IN SQUARE STYLE IN STUDENTS OF SMA NEGERI 1 KETAMBE CLASS XI ACADEMIC YEAR 2022/2023 - Fakhrur Rizal; Orbit Irwansyah; Melfa Br Nababan (CV Naskah Aceh, 2023)
The research is entitled